EVALUATION OF DIETARY SUPPLEMENTATION OF TURMERIC POWDER ON ECONOMIC INDICATORS AND INTESTINAL HISTOLOGY OF BROILERS - H. E. Al Mashhdani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted at the poultry Farm / Animal production department, Collage of Agricultural Engineering Science / University of Baghdad, during the period form 8-3-2014 to 19-4-2014 to evaluation of supplementing different levels of turmeric (curcuma Longa) Powders to Broiler diets on economic indicator and histological measurement of intestine. One hundred and twelve unsexed broiler chicks (Ross 308), one day, 41g its initial body weight. The birds were randomly distributed among Four treatments, each treatment contained 28 birds, with two replicates and each replicate contained 14 birds. The chicks of first treatment (T1) control without supplement, while T2, T3 and T4 treatment were fed a standard diet for broilers in addition to the turmeric powder at levels 0.2, 0.4 and 0.6% 100 kg diet respectively. The results obtained indicated that adding turmeric powder at three different levels in Feed conversion ratio were increase significant (p<0.05) in T3 and T4 compared with T1 while T2 similar with T1 there ware increase significant (p<0.05) in T3, T2 and T4 compared with T1 in Production Index and economic indicator in 42 days. There was increase significant (p<0.05) in the total intestinal wall thickness (duodenum, Jejunum. and ileum) in adding turmeric powder in treatments compared with control group, Villi length and crypts of Lieberkahan depth were higher value for supplemented groups as compared with control it could be concluded from this study that turmeric powder have beneficial effect on production index of broiler.